Investigating the effect of ethical leadership on effectiveness : a case study on the Minister of Finance, Mr. Pravin Jamnadas Gordhan - Olivier, Johan (University of Pretoria, 2014)
Dissertation (MBA)--University of Pretoria, 2013.